Metagenomic Evidence for a Methylocystis Species Capable of Bioremediation of Diverse Heavy Metals - Shi, Ling-Dong; Chen, Yu-Shi; Du, Jia-Jie; Hu, Yi-Qing; Shapleigh, James P.; Zhao, He-Ping (Frontiers in Microbiology, 2019)
Heavy metal pollution has become an increasingly serious problem worldwide. Co-contamination with toxic mercury (Hg) and arsenic (As) presents a particularly difficult bioremediation problem. By oxidizing the greenhouse gas methane, methanotrophs have been demonstrated to have high denitrification activity in eutrophic waters, indicating their possible potential for use in bioremediation of Hg(II) and As(V) in polluted water. Using metagenomics, a novel Methylocystis species (HL18) which was one of the most prevalent bacteria in a CH4-based bio-reactor, is described here. The metagenomic-assembled genome (MAG) HL18 had gene products whose average amino acid identity (AAI) against other known Methylocystis species varied from 69% to 85%, higher than the genus threshold but lower than the species boundary. Genomic analysis indicated that HL18 possessed all the genes necessary for the reduction of Hg(II) and As(V). Phylogenetic investigation of mercuric reductase (MerA) found that the HL18 protein was most closely affiliated with proteins from two Hg(II)-reducing bacteria, Bradyrhizobium sp. strain CCH5-F6 and Paracoccus halophilus. The genomic organization and phylogeny of the genes in the As(V)-reducing operon (arsRCCB) had significant identity with those from a As(V)-reducing bacterium belonging to the Rhodopseudomonas genus. Further analysis found that at least eight genera of methanotrophs possess both Hg(II) and As(V) reductases, illustrating the generally overlooked metabolic potential of methanotrophs. These results suggest that methanotrophs have greater bioremediation potential in heavy metal contaminated water than has been appreciated and could play an important role in the mitigation of heavy metal toxicity of contaminated wastewater.